Inescrutabilidad de la referencia, lenguajes privados y estructura de la mente - César Gómez (Crítica)
In this essay the author proposes an interpretation of Quine´s thesis of inescrutability of reference as an inescrutability of the mental. In order to support his interpretation, Prof. Gómez characterizes reference as an intentional notion. Gómez recalls the differences between ocassion sentences and sentences of the form ‘x is P’. In the last group of sentences, reference appears with the singular term. When we interpret occasion sentences, we need nothing more than to detect its stimulus meaning, but when we seek to interpret sentences of the form ‘x is P’ we shall introduce something more, namely, intentionality; that is, mental events. So Gómez says that inescrutability of reference is nothing more than the impossibility of characterize, from the interpreter´s point of view, mental events using non-mental descriptions. If this is the case, then a manual of translation is just a way of ascribing to speakers mental events as their reason for holding that a certain word refers to a certain object. On this view, two different manuals of translation based upon the same empirical evidence are two different ascriptions of mental events (based on the same empirical ground). If we consider two manuals of translation of spanish based on the same empirical evidence, one of them interpreting the word ‘perro’ as (1) dog and the other as (2) dog-shadow, then we shall not be able to decide which is the correct one. We shall not be able to know whether a speaker speaks spanish or proxy-spanish. Gómez says that the difference between explaining linguistic behaviour or spanish speakers as (1) or as (2) is to make use of different psychophysical laws. But if we consider Davidson identification of mental events with physical events, then the manuals of translation to which (1) and (2) belong must correspond to different physical situations. So it seems that the difference between spanish and proxy-spanish is an ontological one. But Gómez argues that there is not a physical difference between speakers of spanish and of proxy-spanish, since the sole possibility of saying that someone is a proxy-spanish speaker requires to dind the reasons of the intentional behaviour of the speakers of a language L, independently of our knowledge of L. Gómez says that the idea that we could detect the mental events that are the primary reasons of the linguistic behaviour of the speakers of L without understanding L is just an illusion based on the dogma of a mental museum autonomous of language. We cannot ascribe detailed beliefs to the speakers of L without knowing the meanings of the words of L. Gómez concludes that if reference is an intentional notion and we accept the binomial intentionality-theoricity with regard to language, then the under-determination of empirical theories seems to imply the inescrutability of the mental. But a consequence of considering a theory of meaning as composed of mental verbs is that we shall consider it as a psychophysic theory. [G.M. Hurtado]